Edge-Shared [M2Cl10]2- Complexes of Reaction between Oxophilic Group IV Metal and Phosphorus Ylides - Javad Sabounchei, Seyyed; Ahmadi, Mohsen; Shahriary, Parisa (Asian Journal of Chemistry, 2011)
The reactions between oxophilic group 4 metal chlorides, a-keto ylides in THF, led to the formation of titanium, zirconium and hafnium edge-shared [M2Cl10]2- complexes (1a-3d). With adding dimethyl sulfoxide as a ligand to these complexes at room temperature crystalline solid [M(DMSO)8]·4Cl·mH2O·DMSO] (M = Ti (1g), Zr (2g) and Hf (3g); m = 0-3) together with phosphonium salts in mother liquid were formed. Its metal complexes have been characterized by elemental analysis, IR and 1H, 13C and 31P NMR spectroscopy. The dominating coordination structures of 1g-3g are seven-coordinated complexes.